2012
DOI: 10.1002/pen.23353
|View full text |Cite
|
Sign up to set email alerts
|

Physical and dyeing properties of poly(ethylene terephthalate)/montmorillonite nanocomposite filament yarns

Abstract: This research paper describes the generation of poly(ethylene terephthalate) (PET)/organoclay nanocomposite filaments by melt‐spinning method and investigation of their physical and dyeing properties. Two montmorillonite types of clay were modified using an intercalating agent synthesized and PET/organoclay (85/15 wt/wt) master batches were prepared using a corotating intermeshing twin screw extruder. Afterward, nanocomposite filaments containing different amounts of organoclay (0.5–5 wt%) were produced and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…Improved dyeability performance of the PET/organoclay nanocomposite filaments could be attributed to void space generation by the addition of montmorillonite‐type clay into the fibre, as confirmed by our previous work and by Gashti and Moradian . A phthalimide carrier was used in this study, and it was shown that a phthalimide carrier had a strong plasticising effect on the PET fibre, i.e.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Improved dyeability performance of the PET/organoclay nanocomposite filaments could be attributed to void space generation by the addition of montmorillonite‐type clay into the fibre, as confirmed by our previous work and by Gashti and Moradian . A phthalimide carrier was used in this study, and it was shown that a phthalimide carrier had a strong plasticising effect on the PET fibre, i.e.…”
Section: Resultssupporting
confidence: 78%
“…In our previous work , we prepared PET/montmorillonite nanocomposite filaments by using two different types of clay which were modified using an ammonium surfactant, and we investigated their physical and dyeing properties. Dyeings were performed at 100 °C (with/without a carrier) and 120 °C (without a carrier).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good dispersion of layered silicates in PU elastomer nanocomposites has been found to improve mechanical properties, thermal stability, gas barrier properties and flame retardancy, etc. Although several studies have reported on the dyeing of clay or layered‐silicate nanocomposites of polypropylene , polyethylene terephthalate (PET) , polyamide 6 , polylactic acid (PLA) and PU , there is almost no literature reporting on the dyeing of PU/clay in filament form. Therefore, in the current study PU filaments have been modified by the incorporation of nanoclay to increase their dyeability with acid dye, basic dye and reactive dye.…”
Section: Introductionmentioning
confidence: 99%
“…Özen and Güneş stated that organoclay layers formed a temporary network within the PET polymer chains, and this led to the development of the crystalline order and amorphous orientation and to decrease the degree of crystallisation. It was observed that these effects depended on the size of the organoclay layers, the relationship between the polymer chain and organoclay, and the decrease in the crystallinity in the filaments where the partially orientated structure is larger [30].…”
Section: Thermal Propertiesmentioning
confidence: 99%